Pengaruh penggunaan bahan ajar berbasis google sites dengan pendekatan realistic mathematics education untuk meningkatkan pemahaman matematis siswa pada pembelajaran materi penyajian data - Yulianti, Vivian; Novtiar, Chandra (IKIP Siliwangi, 2023)
Research a This n focuses on the effect of using Google Sites-based teaching materials in improving students' mathematical understanding of data presentation learning materials. The research subjects were taken from 30 class VII students at SMPN 15 Cimahi. Teaching Materials are designed using ICT media based on Google Sites. The results of this study indicate that the use of teaching materials can improve students' mathematical understanding, this is indicated by an increase in the average value of students' mathematical understanding before the use of teaching materials, which is equal to 26,633 and after the use of teaching materials that is equal to82,10. In addition, the results of this study indicate that there is an effect of the use of teaching materials on increasing students' understanding of the material for presenting the data, this is based on the results of the calculation of the t-sample test related to the analysis of paired-sample T-test two-sided test obtained tcount = 19.851 and ttable = 2.04523 for a significant level of 5% with df = 29, where 19.851 ≥ 2.04523.